Biofilm formation and antibiotic susceptibility for clinical and environmental isolates of Pseudomonas aeruginosa - Farah Mohommed Saleh; Ghadah Mohommed Saleh (World Journal of Experimental Biosciences, 2015)
Pseudomonas aeruginosa is an emerging opportunistic clinical pathogen. Clinical isolates of P. aeruginosa resist wide spectrum of antibiotics and form biofilm. The comparison study between clinical and environmental of P. aeruginosa in terms of biofilm formation and antibiotic resistance is very scanty. Thus, in current study microtiter plate technique was used to measure the biofilm formation by several clinical and environmental isolates. Moreover, the antibiotic susceptibility of these bacteria was evaluated by VITIK 2 techniques. The relationship between the antibiotic susceptibility and biofilm formation was evaluated for clinical and environmental isolates. Clinical and environmental isolates of P. aeruginosa produced a good amount of biofilm but the clinical isolates produced higher amount of biofilm as compared to environmental isolates. Resistance to antibiotics by clinical isolates was higher than resistance to antibiotics by environmental isolates and the minimum inhibition concentration (MIC) of most antibiotics to clinical isolates was higher than MIC against environmental isolates. Little relationship was observed between the biofilm formation and antibiotic resistance in case of clinical isolates, while no relationship was seen between the antibiotic susceptibility and biofilm formation. It can be concluded that the clinical isolates produced biofilm higher than environmental isolates. The relationship was seen only between the biofilm produced by clinical isolates and antibiotic susceptibility.
Keywords: Biofilm, Clinical isolates, Environmental isolates, Pseudomonas aeruginosa.